Total Phenolic, Flavonoid Contents and Antioxidant Activity of Siraitia grosvenorii Fruits Extracts - Wuttisin, Narunan; Boonsook, Warakarn (Food and Applied Bioscience Journal, 2019)
The fruit of Siraitia grosvenorii (Luo hanguo) is commonly used as a beverage material and traditional medicine. S. grosvenorii has been used in China as a folk remedy for the treatment of common cold, pharyngitis, and pulmonary congestion. Previous studies showed that S. grosvenorii extracts possess properties of anti-asthmatic, anti-cancer, anti-diabetic, anti-obesity, anti-oxidative, anti-inflammation and immunoregulating effects, but the possibility of S. grosvenorii for using as cosmetic ingredient has not been investigated. The purpose of this study was to find a suitable solvent to produce S. grosvenorii extract with contained antioxidant property. S. grosvenorii fruit was extracted by macerating in solvents including distilled water, propylene glycol, 95% ethanol, ethyl acetate, and n-hexane. The extracts were evaluated for their total phenolic content, total flavonoid content, antioxidant activities and physical color properties. The results showed that 95% ethanol extract exhibited the highest total phenolic content (2.387 ± 0.063 mg GAE/mg solid crude) compared to other solvents. However, distilled water extract showed the greatest amount of total flavonoid content (25.229 ± 0.904 µg QE/mg solid crude) and the highest value of antioxidant activities determined by DPPH assay (47.396 ± 1.946 µg TEAC/mg solid crude) and ABTS assay (53.997 ± 0.155 µg AEAC/mg solid crude). These results indicated that the antioxidant activity of S. grosvenorii extracts might be attributed to the presence of flavonoid compounds. It can be concluded that distilled water extract of S. grosvenorii might be suitable to apply as an antioxidant ingredient for further applications.